Haemostatic Failure of Prothrombin Complex Concentrates during Elective Dental Procedure - Blatt, Philip M; Pearsall, Arthur H; Givhan, Edgar G; Hallum, Charles E; Roberts, Harold R; Webster, William P (Thrombosis and Haemostasis, 1979)
One haemophilia A patient with an inhibitor was exposed to a graded surgical procedure and treated with Prothrombin Complex Concentrates (PCC). Hemostasis was not obtained until the inhibitor was neutralized and the patients factor VIII level was normal. This patient is presented to emphasize that PCC are not nearly as effective as once hoped in producing hemostasis in inhibitor patients. Consequently, major decisions should not be made presuming efficacy of these products in inhibitor patients.